Illness and mental illness - Fulford, K; Fulford, Bill KWM (1982)
﻿ The arguments in the literature for and against "mental illness", are shown to founder on the lack of a thorough analysis of the sense of "illness" itself. Such an analysis is developed in the present study in three main stages. STAGE ONE: The ordinary use of "dysfunction" is examined. The term is shown to imply a particular kind of value judgement, derived, in respect of objects, from the purposes of living things for them. STAGE TWO: The sense of "illness" is interpreted from examples of physical illness by comparing and contrasting it with "dysfunction". An important logical link with "action" is identified, which provides an interpretation of the particular kind of negative evaluation implied by "illness". The relationship between "illness" and "disease" is examined in terms of this negative evaluation. STAGE THREE: The results of stage two are generalised from "physical illness" to "mental illness" by way of the notion of "action". "Mental illness" is examined as illustrated by examples of four main kinds of condition - organic psychosis, neurosis, addiction and functional psychosis. In respect of the first of these, "mental illness" is shown to be similar in its logical properties to "physical illness"; in respect of the remaining three, it is shown to be different, but in three quite distinct ways. In each case, however, the properties of "mental illness" are derived consistently with the interpretation of "illness" developed from examples of physical illness in stage two. "Mental illness" and "physical illness" are thus shown to be logically equivalent. In a concluding section, the implications of this result for the debate about "mental illness" are examined.